Encyclopedia of Analytical Chemistry 2020
DOI: 10.1002/9780470027318.a9707
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization and Modification of Chemical Warfare Agents and Their Related Compounds for LC‐MS‐Based Analytical Applications

Abstract: The development of novel analytical methods to detect and identify chemical warfare agents (CWAs), their degradation products, metabolites, and precursors is of high importance as terrorist groups and radical regimes use or plan to use chemical weapons against civilians or military targets. Gas chromatography (GC) and liquid chromatography (LC), usually hyphenated with mass spectrometry (MS), are the major techniques used to detect and identify chemicals of concern according to the chemical convention. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Recently, a summary of all the derivatization studies reported in the literature for the benefit of the LC-MS analysis of chemical warfare agents in the last 15 years was reported by Weissberg et al 30 There is only one report for determining HD in the environment by LC-MS/MS using chemical derivatization in acetonitrile with potassium thioacetate (PTA), which substitutes chloride groups. 31 In general, the replacement of the chloride groups of HD with nucleophilic high ionized groups would be a good concept and has the potential to sensitively detect HD via LC-ESI-MS/MS; however, this derivatization approach cannot reveal the identity of reactive electrophile groups, such as bromide, chloride, or vinyl, which existed prior to the derivatization step.…”
Section: The Major Analytical Challenge Is the Detection And Identification Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a summary of all the derivatization studies reported in the literature for the benefit of the LC-MS analysis of chemical warfare agents in the last 15 years was reported by Weissberg et al 30 There is only one report for determining HD in the environment by LC-MS/MS using chemical derivatization in acetonitrile with potassium thioacetate (PTA), which substitutes chloride groups. 31 In general, the replacement of the chloride groups of HD with nucleophilic high ionized groups would be a good concept and has the potential to sensitively detect HD via LC-ESI-MS/MS; however, this derivatization approach cannot reveal the identity of reactive electrophile groups, such as bromide, chloride, or vinyl, which existed prior to the derivatization step.…”
Section: The Major Analytical Challenge Is the Detection And Identification Ofmentioning
confidence: 99%
“…Recently, a summary of all the derivatization studies reported in the literature for the benefit of the LC‐MS analysis of chemical warfare agents in the last 15 years was reported by Weissberg et al 30 There is only one report for determining HD in the environment by LC‐MS/MS using chemical derivatization in acetonitrile with potassium thioacetate (PTA), which substitutes chloride groups 31 …”
Section: Introductionmentioning
confidence: 99%
“…To verify suspected instances of noncompliance with the treaty, analytical methods that permit the unambiguous identification of chemical warfare agents are required. Gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) are the most widely used techniques for their detection and identification 3,4 . In contrast to the mass spectra of G‐type nerve agents which display informative fragment ions, making their identification straightforward, the identification of V‐type nerve agents is more challenging, due to the existence of structural variations, including isobaric species; in addition, their spectra obtained by electron ionization mass spectrometry (EI‐MS) and electrospray ionization tandem mass spectrometry (ESI‐MS/MS) are dominated by fragments/ions originating mostly from the N,N ‐dialkylaminoethyl moiety; therefore, these agents present MS‐spectral similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) are the most widely used techniques for the discrimination of these compounds, and they are routinely used for their detection and identification. 5 In contrast to G-nerve agents, which present unique structures and fragment ion masses, making their identification straightforward, when analyzing V-nerve agents, structural variations exist, including isobaric species, making their identification more challenging. A few studies have highlighted the utility of MS techniques for the differentiation and identification of V-type nerve agents.…”
Section: Introductionmentioning
confidence: 99%
“…Their mass spectra are dominated by ions originating from the N , N ‐dialkylaminoethyl moiety, and therefore, these agents present highly similar MS spectra. Gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) are the most widely used techniques for the discrimination of these compounds, and they are routinely used for their detection and identification 5 . In contrast to G‐nerve agents, which present unique structures and fragment ion masses, making their identification straightforward, when analyzing V‐nerve agents, structural variations exist, including isobaric species, making their identification more challenging.…”
Section: Introductionmentioning
confidence: 99%